The "Famous Places" of Japanese Buddhism: Representations of Urban Temple Life in Early Modern Guidebooks. (June 2014) - Bond, Kevin
This paper examines the commercial and recreational cultures of the urban Buddhist temple during Japan's Edo or early modern period (1603–1868) as depicted in popular guidebooks to famous places ( meisho ki ). Encouraged by advances in travel and communication, and a vibrant bourgeois culture, meisho guidebooks presented religious sites to the common public not as static, immobile spaces catering only to otherworldly spiritual concerns, but as open and elastic geographies simultaneously offering immediate material rewards and leisurely and commercial attractions to visitors. As unique media of local religion, guidebooks reflect how the reputation and allure of popular Buddhist temples among the general public were driven by the commodification of local legends and objects of worship, as well as material pleasures of religious spaces. This paper argues the importance of guidebooks in the production of public knowledge and expectation about religious sites in early modern Japan. These guides reveal material concerns and entertainment not as having been antithetical to the operation of Buddhist institutions, but rather as supports for the spread of Buddhist teachings and popularization of deity worship among the urban populace.